Experimental Acoustic Life Writing: Gerhard Rühm's Radio Plays. - Arteel, Inge (CounterText, 2019)
In this article I focus on a selection of radio plays by the Austrian author Gerhard Rühm and analyse them from the perspective of life writing, starting with Irene Kacandes' findings on the increased referential effect of experimental life writing (2012). I want to extend the notion of experimental life writing to the medium of the experimental radio play and investigate whether and how the experiments with spoken language, voice, and musicalisation of language contribute to an effect of realness and create an aural world infused with lived experientiality. I'm particularly interested in the relationship between individualised, figurative voices and sounds, as they are to be expected in (auto)biographical art, and the defiguration and deindividualisation in the experimental, synthetic manipulation of human language and voice. Situating the corpus in the history of the German Neues Hörspiel, my analysis hopes to prove that the reality effect of the experimental (auto)biographical radio play does not, or at least not only, refer to an individual biographical self. Instead, the complex constellation of text and paratext, of scripted and spoken language, and of voice and music opens up the referential level for a broader, more general human experientiality. Most importantly, the technical possibilities of the radiophonic medium allow an intricate play with the semantics of referential language, with masking and unmasking voices, and with the exploration of the pathos of speaking together.